Dendritic effect of ligand-coated nanoparticles: enhanced apoptotic activity of silica-berberine nanoconjugates - Halimani, Mahantappa; Chandran, S. Prathap; Kashyap, Sudhir; Jadhav, V. M.; Bhagavatula L. V. Prasad; Hotha, Srinivas; Maiti, Souvik (Langmuir, 2009)
We describe the synthesis and biological characterization of a novel prototype, namely, silica nanoconjugates bearing a covalently linked berberine, a plant alkaloid known to have antiproliferative activity. The effect of synthesized nanoconjugates on cell proliferation, the cell cycle profile, and apoptosis in the human cervical carcinoma cell line (HeLa), human hepatocellular liver carcinoma cell line (HepG2), and human embryonic kidney (HEK) 293T cell line has been studied and compared with the results obtained for free berberine. Our results show that all the nanoconjugates display higher antiproliferative activity than free berberine. The ability of these nanoconjugates to inhibit cellular proliferation is mediated by the cell cycle arrest at the G1 phase. Moreover, silica nanoconugates caused selective apoptotic arrest with a higher efficiency than free berberine followed by apoptotic cell death as shown by quantitative fluorescence-activated cell sorting analyses. Efficiency of the nanoconjugates increases upon an increase in the linker chain length, demonstrating the distinct role of the spacer chain that conjugates nanoparticles and ligands. The actual reason to show enhanced efficiency by the nanoconjugates has not been elucidated in the present study; however, we hypothesize that an increase in local concentration due to the confinement of a ligand on the nanosurface (''dendritic'' effect) might have led to the observed effect.

Direct method for the preparation of glycolipid-metal nanoparticle conjugates: sophorolipids as reducing and capping agents for the synthesis of water re-dispersible silver nanoparticles and their antibacterial activity - Singh, Sanjay; Patel, Pitamber; Jaiswal, Swarna; Prabhune, Asmita; Ramana, C. V.; Bhagavatula L. V. Prasad (New Journal of Chemistry, 2009)
The production of a new class of glycolipid-metal nanoparticle conjugates, namely, sophorolipid reduced/capped silver nanoparticles is demonstrated for the first time, by unveiling the reducing and capping abilities of sophorolipid derived from oleic acid. It is also demonstrated that the sophorolipid capped Ag nanoparticles are highly potent antibacterial agents, against both Gram-positive and Gram-negative bacteria. The utilization of sophorolipid brings out several advantages, such as eliminating the necessity for exogenous reducing agent and imparting better stability to the silver nanoparticles as compared to their oleic acid capped analogues. These sophorolipid capped silver nanoparticles can be obtained as a stable powder that can be re-dispersed in water as desired.

Development of a multifunctional catalyst for a ``relay'' reaction - Ganai, Anal Kumar; Shinde, Pravin; Dhar, Basab B.; Sen Gupta, Sayam; Bhagavatula L. V. Prasad (RSC Advances, 2013)
In the area of catalysis, nanoparticles and enzymes are two of the most important systems. By amalgamating the two, we present here proof of the concept that it is possible to prepare a multifunctional catalyst that can carry out a ``relay'' reaction. The catalyst consists of a surface bound enzyme on a metal(core)-silica(shell) nanoparticle architecture. Here the enzyme catalyzes the 1st reaction and the metal nanoparticles act as a catalyst for the 2nd reaction of the product from the 1st reaction. In particular, we have studied the catalytic activity of glucosidase grafted Au@mSiO(2) on 4-nitrophenyl-beta-glucopyranoside, where glucosidase will catalyse the 1st step to generate 4-nitrophenol, which acts as a substrate for the next reduction step which is catalysed by the Au nanoparticles present inside the mesoporous silica shell.

Dilution does the trick: role of mixed solvent evaporation in controlling nanoparticle self-assembly - Sahu, Puspanjali; Bhagavatula L. V. Prasad (Colloids and Surfaces A-Physicochemical and Engineering Aspects, 2014)
An easy and convenient way to prepare superlattices of amine capped gold nanoparticles is presented. It is clearly established that solvent evaporation significantly influences the nature of resulting superlattices and critically governs whether monolayer or multilayer superlattices are formed. More specifically, it is demonstrated that dilution of the nanoparticle dispersion with a similar solvent (but with different vapour pressure) is an expedient handle to control the nature of self-assembly. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Evaporation rate; gold nanoparticles; Nucleation; Self-assembly

Development of a smart scaffold for sequential cancer chemotherapy and tissue engineering - Sengupta, Poulomi; Agrawal, Vinay; Bhagavatula L. V. Prasad (ACS Omega, 2020)
The fabrication of a dual-functional drug-containing porous polymeric scaffold by layer-by-layer surface modification involving citrate-stabilized gold nanoparticles and cisplatin molecules is being reported. These scaffolds were characterized by electron microscopy and X-ray photoelectron spectroscopy. The capability of the scaffolds to release hydrated cisplatin in a slow and sustained manner over two days is established. Most importantly, the scaffolds turn nontoxic and cell-friendly after drug release, thus allowing the noncancerous fibroblast cells to adhere and proliferate (from 5000 cells to 16,000 cells in 6 days), becoming a potential solution toward an effective drug-carrying scaffold for volume-filling applications. The scaffold-mediated cancer cell killing and fibroblast cell proliferation were confirmed by fluorescence microscopy imaging, flow cytometry, and cell proliferation assays. We surmise that such a dual-purpose (drug-delivery and volume-filler) scaffold could help avoid the multiple surgical interventions needed for tumor surgery and cosmetic corrections. To the best of our knowledge, this is the first example of scaffolds with such a dual functionality which gets manifested in a sequential manner.

Disordered but efficient: understanding the role of structure and composition of the Co-Pt alloy on the electrocatalytic methanol oxidation reaction - Dalavi, Shankar B.; Agarwal, Sheena; Deshpande, Pooja; Joshi, Kavita; Bhagavatula L. V. Prasad (Journal of Physical Chemistry C, 2021)
A systematic investigation of the electrocatalytic Methanol Oxidation Reaction (MOR) was carried out using a model Co:Pt alloy system with different compositions and structural arrangements of the Co and Pt atoms. The structural variations with the same alloy composition included those with disordered arrangement of Co and Pt atoms in a face-centered cubic (fcc) lattice and ordered arrangements in face-centered tetragonal (fct) lattices. Our investigations clearly show that structures with disordered arrangements with Co:Pt atomic ratios near to 1:1 display better electrocatalytic efficiencies even when compared to pure Pt. These experimental findings were then rationalized by means of Density Functional Theory (DFT) calculations. Electronic level signatures in terms of charge transfer and relative shift in the peaks of the d band for surface metal atoms are proposed to be the reasons for the superior catalytic activity of a particular composition over the others. An increase in the number of inequivalent sites for methanol adsorption in disordered systems appears to result in better catalytic performance in comparison with ordered systems.